Role of sevoflurane in myocardial ischemia-reperfusion injury via the ubiquitin-specific protease 22/lysine-specific demethylase 3A axis. Issue 5 (2nd May 2022) - Song, Shan; Wang, Yang; Wang, Hai-Yan; Guo, Long-Long
ABSTRACT: Myocardial ischemia-reperfusion injury (MIRI) represents a coronary artery disease, accompanied by high morbidity and mortality. Sevoflurane post-conditioning (SPC) is importantly reported in myocardial disease. Accordingly, the current study sought to evaluate the role of Sevo in MI/RI. Firstly, MI/RI models were established and subjected to SPC. Subsequently, pathological injury in the myocardium, myocardial infarction areas, H9c2 cell viability, apoptosis, and levels of creatine kinase-MB (CK-MB), cardiac troponin I (cTnI), and lactate dehydrogenase (LDH) were all measured. Ubiquitin-specific peptidase (22USP22), lysine-specific demethylase 3A (KDM3A), and Yes1 associated transcriptional regulator (YAP1) were down-regulated in H9c2 cells using cell transfection to verify their roles. The interaction between USP22 and KDM3A and between KDM3A and YAP1 was further validated. USP 22, KDM3A, and YAP1 were found to be down-regulated in MI/RI and SPC protected MI/RI rats, as evidenced by up-regulated expressions of USP22, KDM3A, and YAP1, reduced pathological injury in the myocardium, myocardial infarction areas, apoptosis, and levels of CK-MB, cTnI, and LDH, and enhanced H9c2 cell viability; while the protective effects of Sevo were counteracted by silencing of USP22, KDM3A, and SPC upregulated USP22, which stabilized KDM3A protein levels via deubiquitination, and KDM3A inhibited histone 3 lysine 9 di-methylation (H3K9me2) levels in the YAP1 promoter to encourage YAP1 transcription, to reduce MI/RI. Graphical Abstract: uf0001